2016
DOI: 10.1039/c6ta08278e
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of solvent and polymer additives on solar cell performance and stability of small molecule bulk heterojunction solar cells

Abstract: The combination of solvent and polymer additives synergistically enhances solar cell performance and the stability of small molecule bulk heterojunction solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…The P3BT polymer heterogeneously nucleates donor crystallites into interconnected nanofibers, to similar effect as the insulating solid additive PS; however, in this ternary blend, P3BT also contributes to photogeneration and charge transport, increasing the hole mobility by an order of magnitude . Lee et al accomplished similar results by combining 2 wt% PCDTBT with 0.4% v/v DIO in the same D:A blend, synergistically improving performance from 2.4% (without either additive) to 7.9% . Significantly, the ternary blend morphology was less sensitive to thermal treatment and the concentration of solvent additive, as observed for other binary additive combinations .…”
Section: Future Of Solvent Additive Processing In Organic Photovoltaicsmentioning
confidence: 89%
See 1 more Smart Citation
“…The P3BT polymer heterogeneously nucleates donor crystallites into interconnected nanofibers, to similar effect as the insulating solid additive PS; however, in this ternary blend, P3BT also contributes to photogeneration and charge transport, increasing the hole mobility by an order of magnitude . Lee et al accomplished similar results by combining 2 wt% PCDTBT with 0.4% v/v DIO in the same D:A blend, synergistically improving performance from 2.4% (without either additive) to 7.9% . Significantly, the ternary blend morphology was less sensitive to thermal treatment and the concentration of solvent additive, as observed for other binary additive combinations .…”
Section: Future Of Solvent Additive Processing In Organic Photovoltaicsmentioning
confidence: 89%
“…In films cast from 3% v/v DIO, overcrystallization could be suppressed by increasing the polymer concentration to 20 wt%—maintaining a PCE of 6.6%, compared to 2.5% without the additional polymer donor. Additionally, Lee et al showed that PCDTBT's ability to nucleate p ‐DTS(FBTTh 2 ) 2 stems from favorable interactions between benzothiadiazole subunits, suggesting future criteria for controlling morphology via ternary components . As a final example, Zhang et al combined 3% v/v DIO with 15 donor wt% p ‐DTS(FBTTh 2 ) 2 as a sensitizer for PTB7‐Th:PC 71 BM blends to achieve 10.5% PCE .…”
Section: Future Of Solvent Additive Processing In Organic Photovoltaicsmentioning
confidence: 99%
“…[47] Slow solvent evaporation facilitates the formation of interpenetrating donoracceptor networks in the BHJ film. [22,[48][49][50] On the mesoscale, the morphology changes of printed films are tracked by in situ GISAXS measurements. [40,51,52] On this scale, the initial states of liquid solution films on the solid substrate are prone to radiation damage by the intense X-ray beam.…”
Section: (3 Of 7)mentioning
confidence: 99%
“…Organic molecules with donor‐acceptor (D–A) architect find uses in the area of organic solar cells (OSCs), organic light‐emitting diodes (OLEDs), organic photovoltaics (OPVs), organic thin‐film transistors (OTFTs), two‐photon absorption (2PA), photodynamic therapy, ion‐sensing, cell imaging, fluorescent molecular rotors (FMR's) and non‐linear optical (NLO) materials . Efforts are made to diversify the D–A materials by designing and synthesizing a wide spectrum of dipolar, quadrupolar, octupolar and multi‐branched chromophores .…”
Section: Introductionmentioning
confidence: 99%